2008
DOI: 10.1007/s10712-008-9044-0
|View full text |Cite
|
Sign up to set email alerts
|

Global Soil Moisture Patterns Observed by Space Borne Microwave Radiometers and Scatterometers

Abstract: Within the scope of the upcoming launch of a new water related satellite mission (SMOS) a global evaluation study was performed on two available global soil moisture products. ERS scatterometer surface wetness data was compared to AMSR-E soil moisture data. This study pointed out a strong similarity between both products in sparse to moderate vegetated regions with an average correlation coefficient of 0.83. Low correlations were found in densely vegetated areas and deserts. The low values in the vegetated reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(179 citation statements)
references
References 66 publications
9
169
0
1
Order By: Relevance
“…However, numerous studies in the past have shown that satellite-derived surface soil moisture is strongly related to the 0-0.05 m soil layer (e.g. Wagner et al, 2007;De Jeu et al, 2008;Draper et al, 2009;Gruhier et al, 2010). Therefore in GLEAM, satellite observations of soil moisture (Ξ) are assimilated with the modelled water content of the first soil layer (w (1) ) that is predicted by Eq.…”
Section: Satellite Surface Soil Moisture Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous studies in the past have shown that satellite-derived surface soil moisture is strongly related to the 0-0.05 m soil layer (e.g. Wagner et al, 2007;De Jeu et al, 2008;Draper et al, 2009;Gruhier et al, 2010). Therefore in GLEAM, satellite observations of soil moisture (Ξ) are assimilated with the modelled water content of the first soil layer (w (1) ) that is predicted by Eq.…”
Section: Satellite Surface Soil Moisture Assimilationmentioning
confidence: 99%
“…This implies that the value of K will be fully determined by the estimation of the variance error in the microwave observations (V ). According to De Jeu et al (2008), the vegetation optical depth (τ ) can be used to approximate the polynomial relation existing between the uncertainty of the microwave soil moisture retrieval and the vegetation density. This relation can be described as…”
Section: Satellite Surface Soil Moisture Assimilationmentioning
confidence: 99%
“…Total water storage estimates derived from missions like the Gravity Recovery and Climate Experiment [Tapley et al, 2004] provide a unique opportunity to observe initial catchment state over large areas in a way that can be combined with models [Van Dijk et al, 2011a]. Optical and passive and active microwave remote sensing can also help to improve model estimates of initial snow cover and shallow soil moisture state [Andreadis and Lettenmaier, 2006;de Jeu et al, 2008;Liu et al, 2012].…”
Section: Actual Forecast Skillmentioning
confidence: 99%
“…Advances and new developments in monitoring of soil moisture (de Jeu et al 2008;Liu et al 2009), precipitation, andevapotranspiration (Anderson andKustas 2008;Kalma et al 2008) provide crucial elements to help constrain space-time trends in groundwater recharge. Future research will undoubtedly focus on the further integration of these multi-platform and multi-parameter observations, including GRACE data, in extensive hydrological models.…”
Section: Remote Sensing Of Space-time Trendsmentioning
confidence: 99%